Effect of Oral and Intramuscular Administration of Ivermectin in Guinea Pigs on Survival of Blood-feeding Anopheles stephensi under Insectary Conditions - Nima Danaei; Seyed Hassan Moosa-Kazemi; Mohammad Mehdi Sedaghat; Hamid Reza Basseri; Safdar Masoumi (Journal of Mazandaran University of Medical Sciences, 2020)
Background and purpose: Insecticide resistance in mosquitoes particularly malaia may lead to reemergence of malaria epidemics. This study aimed to investigate the effect of oral and intramuscular administration of ivermectin on guinea pigs exposed to Anopheles stephensi mosquitoes, the main malaria vector. Materials and methods: The effect of ivermectin was studied in oral and intramuscular administrations (treatment groups), and untreated (control group), on guinea pigs exposed to 750 Anopheles stephensi mosquitoes. The experiments were done at larval, hatching eggs and pregnancy stages in insectary condition at the School of Public Health, Tehran University of Medical Sciences, 2018. Results: After 24-hours of blood feeding, the mortality rates of An.  stephensi were 74.19% and 66.4% in animals with intramuscular and oral administration of ivermectin, respectively, which were significantly different with that of the control group (2.80%) (P< 0.001). The rates of infertility in two experimental groups were 63.63% and 45.23%, respectively and in control group it was 19.42% (P< 0.001). Infertility was found to be significantly different between the experimental groups and the control group (P<0.001). Conclusion: According to this study, ivermectin was effective in decreasing the survival of Anopheles stephensi. therefore, it is suggested to be evaluated in field conditions.